Solidariedade atlântica: movimento brasileiro em apoio às independências africanas, entre percursos e conexões (1961-1975) - Viviane de Souza Lima (2017)
This study aims to show how the Brazilian movement in support of African independence, created in the 1960s, was able to shape a network of solidarity with the African nationalist movements, especially the MPLA, and give greater visibility to the struggle for independence in the Portuguese colonies, mainly in Angola. The Movimento Afro-Brasileiro Pró-Libertação de Angola (MABLA) brought together Brazilians, Africans and Portuguese anti-Salazarists and worked mainly in the cities of São Paulo and Rio de Janeiro. MABLA was a movement of mobile configuration that brought together supporters of diverse ideological tendencies around a common project: the defense of the independence of the African peoples.